2019
DOI: 10.19030/jaese.v6i1.10288
|View full text |Cite
|
Sign up to set email alerts
|

A Logistic Regression Model Comparing Astronomy And Non-Astronomy Teachers In Québec’s Elementary Schools

Abstract: Based on the results of an online survey of 500 Québec’s elementary (K-6) teachers conducted in 2015 that probed the way respondents teach astronomy to their classrooms, their background in S&T, their pre-service education, their aims and goals for astronomy teaching, their attitude toward teaching astronomy, the resources and materials they use, their view on the effectiveness of pre- and in-service training, and their need for in-service training, we present a logistic regression model comparing elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Dans son dernier bilan, le CSE constatait que « la science demeure, encore aujourd'hui et dans bien des écoles, une discipline passablement délaissée » (CSE, 2013, p. 2). Cette situation s'expliquerait en partie par la perception qu'ont de nombreuses personnes enseignantes du primaire que l'enseignement de la ST est complexe et exige du temps, du matériel et des connaissances disciplinaires qui leur font défaut (Chastenay, 2018 ;Chastenay et Riopel, 2019). Il en résulterait un déplaisir et un inconfort marqués face à l'enseignement de la ST (Chastenay, 2018 ;Chastenay et Riopel, 2019 ;Hasni, 2005), menant à un désintérêt et à un désengagement plus ou moins importants (Avraamidou, 2014 ;Bleicher, 2007 ;Carrier et al, 2017 ;King et al, 2001), ainsi qu'à une attitude généralement négative envers cette matière et son enseignement (Akerson et Flanigan, 2000 ;Goodrum et al, 2001 ;Jarvis et Pell, 2004 ;Palmer, 2004 ;Walma van der Molen et al, 2010).…”
Section: Introductionunclassified
“…Dans son dernier bilan, le CSE constatait que « la science demeure, encore aujourd'hui et dans bien des écoles, une discipline passablement délaissée » (CSE, 2013, p. 2). Cette situation s'expliquerait en partie par la perception qu'ont de nombreuses personnes enseignantes du primaire que l'enseignement de la ST est complexe et exige du temps, du matériel et des connaissances disciplinaires qui leur font défaut (Chastenay, 2018 ;Chastenay et Riopel, 2019). Il en résulterait un déplaisir et un inconfort marqués face à l'enseignement de la ST (Chastenay, 2018 ;Chastenay et Riopel, 2019 ;Hasni, 2005), menant à un désintérêt et à un désengagement plus ou moins importants (Avraamidou, 2014 ;Bleicher, 2007 ;Carrier et al, 2017 ;King et al, 2001), ainsi qu'à une attitude généralement négative envers cette matière et son enseignement (Akerson et Flanigan, 2000 ;Goodrum et al, 2001 ;Jarvis et Pell, 2004 ;Palmer, 2004 ;Walma van der Molen et al, 2010).…”
Section: Introductionunclassified
“…For example, in the United States, the sixth edition of the National Survey of Science and Mathematics Education (NSSME+) found that a majority of elementary teachers still mainly use science textbooks to teach science in their classroom (Banilower et al, 2018;Plumley, 2019), a result that has remained more or less constant over the last 40 years (see http://horizon-research.com/NSSME/). Similar results were found by Rowell and Ebbers (2004) in Alberta, Canada, and across four decades by the Conseil supérieur de l 'éducation 1982;1990;2013 in Québec, Canada. A recent survey conducted by the author with 638 elementary teachers found that most teachers use textbooks and exercise books almost exclusively to teach science to their students, thus transforming the study of science content into a reading and writing exercise (Chastenay, 2014(Chastenay, , 2018Chastenay and Riopel, 2019).…”
Section: Introductionmentioning
confidence: 99%